Detection of Sub‐Terahertz Raman Response and Nonlinear Optical Effects for Luminescent Yb(III) Complexes. Issue 2 (1st November 2021) - Kumar, Kunal; Stefanczyk, Olaf; Nakabayashi, Koji; Imoto, Kenta; Oki, Yurie; Ohkoshi, Shin‐ichi
Abstract: The development of multifunctional oriented polar crystals combining diverse optical, nonlinear optical, and magnetic phenomena are desirable. Two enantiomorphic assemblies [Yb III (TPPO)3 (NCE)3 ] (E = S ("YbS "), Se ("YbSe "); TPPO = triphenylphosphine oxide) are prepared. Both crystallites show ultralow‐frequency (ULF) Raman scattering for molecular materials with a value of 16 cm −1 (0.48 THz), originating from collective vibrations of the TPPO ligand and pseudohalides, which is supported by ab initio calculations. Moreover, YbS and YbSe crystals exhibit high‐intense second harmonic generation (SHG) phenomena along the threefold rotation c ‐axis. The polarization‐variation of the pumping laser electric field experiment performed on single crystals gives a unique insight into the tensor elements constituting the R 3 space group. Replacement of thiocyanide with selenocyanide in YbSe compound increases the second harmonic signal attributed to increased polarization. Besides, they also exhibit 4 f ‐metal centered high‐performance near‐infrared luminescence thermometric properties and weak single‐molecule magnet behaviors. They can also serve as a platform to study the magnetic and linear/nonlinear optical cross effects. Abstract : Two chiral compounds containing pseudohalides are prepared, which exhibit Raman shift in the sub‐terahertz region. They also reveal second‐harmonic generation properties in the powder and single‐crystal forms comparable to potassium dihydrogen phosphate standard. Additionally, the presence of Yb(III) ions facilitates ratiometric thermometer behavior in the near‐infrared region and reveals dynamic magnetic properties upon applied dc field.